Phytoplankton primary production in freshwater environments of Argentina - Villafañe, Virginia Estela (2014)
In this article we review the existing knowledge about phytoplankton primary production (PPP)  studies conducted in freshwater environments of Argentina, as well as the methodologies used to assess it. The large geographical and temporal differences in physical, chemical and biological characteristics of the aquatic bodies have resulted in a wide range of PPP values. This, together with the different methodologies and approaches used to assess PPP, precluded for the determination of spatial and temporal trends. In regard to PPP studies, and when looking at the water bodies in Argentina as a whole, it is evident that lakes have been scattered sampled; moreover, information about rivers and streams is scarce or virtually absent. These facts clearly highlight for the need of continuing (in some cases) or starting (in most of the cases) monitoring programs of PPP (as well as of related variables) to further assess the impacts of human activities on aquatic bodies i.e., as those occurring due to climate change.